Comparative in vitro activity of oral antimicrobial agents against Enterobacteriaceae from patients with community-acquired urinary tract infections in three European countries. (January 2016) - Kresken, M.; Körber-Irrgang, B.; Biedenbach, D.J.; Batista, N.; Besard, V.; Cantón, R.; García-Castillo, M.; Kalka-Moll, W.; Pascual, A.; Schwarz, R.; Van Meensel, B.; Wisplinghoff, H.; et al.
Abstract: Enterobacteriaceae causing community-acquired urinary tract infections were examined in selected outpatient clinics and hospitals in Belgium, Germany and Spain using EUCAST breakpoints for susceptibility. A total of 1190 isolates were collected. Escherichia coli isolates were resistant to amoxicillin–clavulanic acid (28.1%), ciprofloxacin (23.4%) and trimethoprim–sulfamethoxazole (21.4%) compared with fosfomycin and nitrofurantoin (each, <1.5%). Ceftibuten (MIC50/90 0.25/0.5 mg/L) and ceftriaxone activity (MIC50/90 ≤0.25 mg/L) was comparable. Ceftibuten (MIC90 ≤0.25 mg/L) was also active against Proteus mirabilis and Klebsiella spp. Extended-spectrum β-lactamase phenotypes were 7.1% for E. coli, 5.6% for Klebsiella pneumoniae and 0.4% for P. mirabilis . Resistance was common among men and elderly women.